Development of electrodynamics transducer for solid particle measurement - Norhaslinda, Mohd Rosli (2012)
The electrostatic sensor was used in process industry because low cost and robust. Electrostatic charge can be detected using sensing device or called as electrode sensor and convert into voltage using associated electronic or known as electrodynamics transducer.The sensing device or electrode sensor consists of a conductor, insulated from the pipeline which may take a variety of different shapes and sizes. The associated electronics is a circuit for signal conditioning to invert the voltage. In the pipeline system, non-intrusive electrode sensor was assembled or implemented. Movement of solid particles which is sand will generate electrostatic charges and can be detect using sensing device or electrode and convert into voltage by electrodynamics transducer or associated electronic. The pipeline system will develop for solid particle flow and the electrodynamics transducer for signal conditioning circuit. The three outputs are amplified voltage, rectified voltage and average voltage will captured and analysis by oscilloscope.